The role of ureteroscopy as a diagnostic and therapeutic tool in various indications - (:unkn) unknown (Springer Netherlands, 1994)
Ureteroscopy is now in routine use for the diagnosis and treatment of various pathologies in the upper urinary tract. We report here on our experience in diagnostic and therapeutic applications of the 11.5 F rigid ureteroscope in 85 patients and 88 ureters. An overall success rate of 68.18% (60/88) was achieved when therapeutic and diagnostic interventions were evaluated together. Success rate was 66.65% in the treatment of ureteral stones (all locations), 100% in the removal of retained catheters, and 81.82% in diagnostic interventions. Frequencies of complications like postoperative fever, stone migration, and various degrees of ureteral perforation were 5.68%, 5.68%, and 7.95%, respectively, consistent with current literature. We conclude that rigid ureteroscopy can be safely applied for appropriate indications in the hands of competent urologists. © 1994 Akadémiai Kiadó.